Stochastic Assessment of Nonpoint Source Contamination: Joint Impact of Aquifer Heterogeneity and Well Characteristics on Management Metrics - Vincent Henri, Christopher; Harter, Thomas (Water resources research, 2019)
Nonpoint source (NPS) groundwater contamination in sedimentary basin aquifers with overlying agricultural activities increasingly threatens groundwater supplies. The role of aquifer heterogeneity has not been well understood in the assessment of NPS and in linking pollution sources to impacts in water supply wells. A typical well taps into and mixes groundwater varying in age by decades or even centuries. This study investigates the joint impact of aquifer heterogeneity and pumping well characteristics (well depth, pumping rate, and screen length) on expected values of and uncertainty about key management metrics: (1) travel time of a NPS contaminant to a production well, (2) spatiotemporal characteristics of the source area, and (3) contaminant compliance at production wells. A stochastic approach is employed using Monte Carlo simulation of flow and nonreactive transport in 3‐D highly heterogeneous alluvial aquifer systems. Well design is shown to dominate the distribution of travel time mixing and the overall location and spread of the source area. Larger extraction intensity and closer proximity to the land surface are shown to significantly suppress effects of large aquifer heterogeneity on uncertainty on all metrics. Deep wells and wells with lower pumping rates have more uncertain source areas. Long‐term NPS contaminants with high source concentration (>10 times compliance level) will be exceeded in most wells within decades, while low‐intensity source concentrations (2–4 times compliance level, typical for nitrate and salinity) have large uncertainty about time to exceedance suggesting wide variability among a set of wells with similar well design subject to the same NPS pollution. Key Points Management metrics for nonpoint source (NPS) pollution of large production wells are assessed stochastically Well characteristics (pumping rate and depth) significantly impact statistics and uncertainty Extraction intensity and proximity to the NPS suppress the potential for heterogeneity to generate uncertainty